A chromosomal-level reference genome of the widely utilized Coccidioides posadasii laboratory strain "Silveira". Issue 4 (7th February 2022) - de Melo Teixeira, Marcus; Stajich, Jason E; Sahl, Jason W; Thompson, George R; Brem, Rachel B; Dubin, Claire A; Blackmon, Austin V; Mead, Heather L; Keim, Paul; Barker, Bridget M
Abstract: Coccidioidomycosis is a common fungal disease that is endemic to arid and semi-arid regions of both American continents. Coccidioides immitis and Coccidioides posadasii are the etiological agents of the disease, also known as Valley Fever. For several decades, the C. posadasii strain Silveira has been used widely in vaccine studies, is the source strain for production of diagnostic antigens, and is a widely used experimental strain for functional studies. In 2009, the genome was sequenced using Sanger sequencing technology, and a draft assembly and annotation were made available. In this study, the genome of the Silveira strain was sequenced using single molecule real-time sequencing PacBio technology, assembled into chromosomal-level contigs, genotyped, and the genome was reannotated using sophisticated and curated in silico tools. This high-quality genome sequencing effort has improved our understanding of chromosomal structure, gene set annotation, and lays the groundwork for identification of structural variants (e.g. transversions, translocations, and copy number variants), assessment of gene gain and loss, and comparison of transposable elements in future phylogenetic and population genomics studies.